When the dogs ate candles : a time in El Salvador - Hutchinson, Bill, 1947- (University Press of Colorado, 1998)
When the Dogs Ate Candles: A Time in El Salvador follows one U.S. citizen as the journeys into the terrible reality of El Salvador in the 1980s, a reality that made the term "death squad" common in the English-speaking world. Galvanized by what he learned in a chance encounter in 1986, the author, Bill Hutchinson, undertook a novel strategy to protect human rights workers in El Salvador. Called "the Accompaniment Project," the plan brought U.S. volunteers to El Salvador to remain by the side of Salvadorans involved in human rights work. This is also the story of Salvadorans who stood up to a barbaric regime: the savage torture of Mirtala Lopez, a teenaged leader of a refugee organization who survived to continue her work among the displaced; the human rights work of Herbert Anaya, leader of the Non-Governmental Human Rights Commission of El Salvador, who was assassinated in 1987; and the testimony of an embittered army defector, Cesar Vielman Joya Martinez, who escaped to the U.S. to tell that his unit operated as a clandestine death squad unit using funds provided by U.S. supervisors. U.S. citizens are also here: Brian Willson, the Vietnam veteran who lost his legs when he sat in front of a munitions train, and Rep. Barbara Boxer (D-CA) who carried photographic evidence of the war's savagery to the floor of the House. -- Provided by publisher